2014
DOI: 10.1186/2045-3701-4-50
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative ductular reactions correlate with hepatic progenitor cell and predict recurrence in HCC patients after curative resection

Abstract: BackgroundDuctular reactions (DRs) are well documented in many acute and chronic liver disease.The DRs are thought to be the transit amplifying cells deriving from activation of the stem/progenitor cell compartments of the liver. The aim of this study was to examine the presence of proliferative index of DR (PI-DR) and HPC markers’ expression in HCCs after curative hepatectomy, as well as their relationship with clinicopathological features and prognosis.ResultsTissue microarray with peritumoral and intratumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…The number of Shh-expressing hepatocytes correlates with fibrosis severity, and the severity of the ductular reaction (Guy et al, 2012; Machado et al, 2015) which is known to associate with fibrogenesis and carcinogenesis (Richardson et al, 2007; Ye et al, 2014). Once the Hh pathway is activated, it can induce a strong self-perpetuating response.…”
Section: Hedgehog Pathway In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…The number of Shh-expressing hepatocytes correlates with fibrosis severity, and the severity of the ductular reaction (Guy et al, 2012; Machado et al, 2015) which is known to associate with fibrogenesis and carcinogenesis (Richardson et al, 2007; Ye et al, 2014). Once the Hh pathway is activated, it can induce a strong self-perpetuating response.…”
Section: Hedgehog Pathway In Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…OV6 positive cells were found in some locations, such as in hepatic cords, undifferentiated cell at the sinusoidal end of hepatocytes and in bile ductal cells in the portal tract. Similarly, Ye et al (2014) found that OV6positive cells similar to the oval cells adjacent to ducts. Co-expression between OV6 and CK19 were also observed.…”
Section: Discussionmentioning
confidence: 74%
“…HPCs also express cholangiocytes markers (CK19) moderately and HSCs marker (CD45 and CD109) strongly. Akiba et al (2013) CD56, c-kit (CD117), CD133, EpCAM Badrawy et al (2013) OV6, AFP Chen et al (2015) OV6, CK19 Hao et al (2013) EpCAM, CD133, AFP, EFNA1 Jia et al (2013) OV6 Li et al (2014) Alb, AFP, CK8, CK18, CK19, CD90, c-kit (CD117), OV6, CD45, CD109 Libbrecht et al (2000) CK7, CK19, CK8, CK18, Chrom-A, OV6 Petersen et al (1998) AFP, GGT, OV6, CK19, OC2, Thy-1 Van Den Heuvel et al (2001) OV6, CK19 Ye et al (2014) EpCAM, OV6, CD133, c-kit (CD117) Yun et al (2013) CK19, Oct-3/4, EpCAM, DLK1 Yovchev et al (2007) EpCAM, CD44, CD24, CD133 In addition, Ye et al (2014) used four markers for HPCs (EpCAM, OV6, CD133 and c-kit) and found that HPCs express HSCs marker (c-kit and CD133) and express biliary marker (EpCAM). Another HSCs marker used to identify HPCs was Thy-1 (Petersen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is logical to assume that paracrine factor secretion by RDs is implicated in liver diseases and carcinogenesis. In addition, it has been demonstrated that proliferation of ductular reactions is positively associated with poor prognosis of adult HCC . Based on these reports, we hypothesized that RDs that express paracrine factors are correlated with angiogenesis and tumoral proliferation in the setting of pediatric liver cancer.…”
Section: Discussionmentioning
confidence: 93%